Wolbachia in guilds of Anastrepha fruit flies (Tephritidae) and parasitoid wasps (Braconidae) - Mascarenhas, Rodrigo O.; Prezotto, Leandro F.; Perondini, Andrï¿½ Luiz P.; Marino, Celso Luiz [UNESP]; Selivon, Denise (My University, 2016)
The endosymbiont Wolbachia is efficiently transmitted from females to their progenies, but horizontal transmission between different taxa is also known to occur. Aiming to determine if horizontal transmission might have occurred between Anastrepha fruit flies and associated braconid wasps, infection by Wolbachia was screened by amplification of a fragment of the wsp gene. Eight species of the genus Anastrepha were analyzed, from which six species of associated parasitoid wasps were recovered. The endosymbiont was found in seven Anastrepha species and in five species of braconids. The WSP Typing methodology detected eight wsp alleles belonging to Wolbachia supergroup A. Three were already known and five were new ones, among which four were found to be putative recombinant haplotypes. Two samples of Anastrepha obliqua and one sample of Doryctobracon brasiliensis showed multiple infection. Single infection by Wolbachia was found in the majority of samples. The distribution of Wolbachia harboring distinct alleles differed significantly between fruit flies and wasps. However, in nine samples of fruit flies and associated wasps, Wolbachia harbored the same wsp allele. These congruences suggest that horizontal transfer of Wolbachia might have occurred in the communities of fruit flies and their braconid parasitoids.
Keywords: Bacteria; Fruit flies; Horizontal transmission; Recombination; Wsp gene